Small bowel obstruction due to splenosis few years after splenectomy : A Case Report . - Khaled.S.Alsherif (Benghazi University Medical Journal, 2026)
Small bowel obstruction secondary to abdominal splenosis is a rare clinical condition that may occur many years after splenectomy and often presents a diagnostic challenge. We report the case of a patient who presented with features of acute small bowel obstruction ten years following splenectomy. The patient had a history of prior splenic surgery and no other significant abdominal pathology. Contrast-enhanced computed tomography of the abdomen revealed multiple well-defined intra-abdominal nodules consistent with splenosis, associated with signs of mechanical small bowel obstruction. Given the persistence of obstructive symptoms, the patient underwent exploratory laparotomy. Intraoperatively, multiple ectopic splenic implants were identified within the peritoneal cavity, with dense adhesions causing small bowel obstruction. Adhesiolysis and excision of the obstructing splenic tissue were performed. Postoperative recovery was uneventful, with complete resolution of symptoms. Histopathological examination confirmed the presence of ectopic splenic tissue consistent with splenosis. The patient remained asymptomatic on follow-up. This case highlights the importance of considering abdominal splenosis in the differential diagnosis of small bowel obstruction in patients with a history of splenic injury or splenectomy. Early recognition using appropriate imaging modalities may aid diagnosis, while surgical management remains the definitive treatment in symptomatic cases.